The Effect of Job Stress and Job Satisfaction on Customer Service Quality Through Organizational Commitment: Study of BPRS in Semarang - Nabila Irgi Rahmawati; Widya Prananta (Lembaga Penelitian dan Pengembangan Masyarakat IAINU Kebumen, 2026)
This research explores how job stress and job satisfaction relate to customer service quality within Bank Pembiayaan Rakyat Syariah (BPRS) in Semarang City, with organizational commitment examined as an intervening variable. A quantitative survey was conducted involving 101 employees who are directly engaged in customer service activities and have worked for at least six months. The data were processed using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS 4.0. The empirical findings reveal that job stress and job satisfaction significantly influence organizational commitment. However, neither variable demonstrates a direct impact on customer service quality. In addition, organizational commitment does not significantly predict customer service quality and does not function as a mechanism of mediating between independent variables and customer service quality. These results suggest that while internal employee conditions contribute to strengthening commitment, service performance in Islamic rural banking institutions may depend more on structural, managerial, or operational factors beyond the variables examined in this study.